Teaching Russian To Students With Modern Smart Technologies: Strategies, Tools, And Best Practices - Madina Jabborova (Next Scientists International Journal EIJP, 2026)
This article examines effective use of modern smart technologies in teaching Russian, presenting pedagogical principles, tools, and practical recommendations. It analyzes mobile apps, adaptive platforms, speech-recognition software, AI chatbots, VR/AR, corpora, and LMS integration, outlining assessment methods and teacher professional development. Challenges such as equity, privacy, content quality, and overreliance on technology are discussed. The paper offers a step-by-step institutional implementation roadmap, sample lessons, and curated resources to support personalized learning and communicative competence. Emphasizing blended pedagogy, immediate feedback, and data-informed interventions, the approach aims to boost learner motivation, accelerate vocabulary and grammar acquisition, and enhance oral and written skills.